Ventilator TBL - Alisa Wray; Shannon Toohey (eScholarship Publishing, University of California, 2017)
Audience: This modified TBL is appropriate for senior medical students, interns, junior and senior emergency medicine residents. Introduction: Ventilator management can be very complex and difficult to understand, much less master. Often, emergency medicine residents and physicians rely on the respiratory therapist to help guide ventilator settings; however, it is important for physicians to understand ventilator settings and management for acute lung protective and obstructive care. Objectives: At completion of this TBL the learner should be able to: 1. Choose appropriate ventilator settings and adjustments for a patient with lung injury or obstructive lung pattern 2. Troubleshoot an alarming ventilator 3. Set up the most common ventilator in their ED 4. Set up the equipment needed for transtracheal jet ventilation. Methods: This is a combination of a modified TBL with small group hands-on ventilator and transtracheal jet ventilation set up and instruction.